The solution of the dual matrix equation A^tX+X^TA=D - Min Zeng; Yongxin Yuan (Kuwait Journal of Science)
The solvability conditions for the dual matrix equation A^tX+X^TA=D are deduced by applying the singular value decomposition, and the expression of the general solution to this dual matrix equation is presented. Furthermore, the minimum-norm solution of this dual matrix equation is also provided. Finally, a numerical example is presented to show the correctness of our results.